UPAYA PENINGKATAN MINAT BACA MAHASISWA: STUDI KASUS PADA PERPUSTAKAAN STMIK AKAKOM YOGYAKARTA - Sri Wahyuni (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
Student's low interest in reading raises concerns for libraries. With such circumstances it is appropriate if the library STMIK AKAKOM give more attention so that the business arise to increase interest in reading. This study aims to determine the efforts that have been done STMIK AKAKOM library in improving students' reading interest. In addition, this study also aims to determine the inhibiting factors that affect reading interest of students. This research can be categorized as case study. This type of research is descriptive qualitative research. Data collection techniques used in this study are observation, interview and documentation. The results showed that the library has made efforts in increasing the interest of reading students, among others, providing a representative means of infrastructure, providing a collection tailored to the needs of pemustaka, providing services beraryintasi on pemustaka satisfaction, held a library promotion, collaborate with others, improve the quality of resources Human, and provide regular funds for library management. The results of this study also show that there are five inhibiting factors that influence reading interest of students is the perception that still consider the library only as a book storage, the perception when dealing with the library is a difficult thing, the comparison of the number of collections with the number of students not in accordance with the standards Applicable, not fully supported by all parties, lack of library socialization through user education activities and information literacy activities that should be held regularly and continuously.